2011
DOI: 10.1371/journal.pone.0017632
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Amyloid in Cell Aggregation and Biofilm Formation

Abstract: Cell adhesion molecules in Saccharomyces cerevisiae and Candida albicans contain amyloid-forming sequences that are highly conserved. We have now used site-specific mutagenesis and specific peptide perturbants to explore amyloid-dependent activity in the Candida albicans adhesin Als5p. A V326N substitution in the amyloid-forming region conserved secondary structure and ligand binding, but abrogated formation of amyloid fibrils in soluble Als5p and reduced cell surface thioflavin T fluorescence. When displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
246
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(256 citation statements)
references
References 54 publications
(113 reference statements)
10
246
0
Order By: Relevance
“…To start cell adhesion, Als proteins undergo conformational changes, accompanied by surface protein clustering, that spread around the entire surface of the cells (73,75). These adhesin clusters, called nanodomains, are force induced (76,77) and are composed of adhesion molecules aggregated through side chain amyloid-like interactions on the cell surface (74,78). This clustering is possible even though Als adhesins are anchored to the cell wall polysaccharide, since it is facilitated by the length and conformational flexibility of their extended molecules (73,74).…”
Section: Surface-associated Proteins With Amyloidogenic Propertiesmentioning
confidence: 99%
“…To start cell adhesion, Als proteins undergo conformational changes, accompanied by surface protein clustering, that spread around the entire surface of the cells (73,75). These adhesin clusters, called nanodomains, are force induced (76,77) and are composed of adhesion molecules aggregated through side chain amyloid-like interactions on the cell surface (74,78). This clustering is possible even though Als adhesins are anchored to the cell wall polysaccharide, since it is facilitated by the length and conformational flexibility of their extended molecules (73,74).…”
Section: Surface-associated Proteins With Amyloidogenic Propertiesmentioning
confidence: 99%
“…Als5-mediated remodeling is independent of cellular metabolic activity, because the protein shows the same behavior in heat-killed cells, which are no longer metabolically active. Remarkably, a single-site mutation in the conserved amyloidforming sequence of the protein has revealed that amyloid interactions represent the driving force that underlies Als5 clustering (Garcia et al, 2011). Hence, the strength of yeast cell-cell adhesion results from the force-induced amyloid-like clustering of hundreds of proteins on the cell surface to form arrays of ordered multimeric binding sites (Lipke et al, 2012).…”
Section: Force-induced Clustering Of Cell Adhesion Proteinsmentioning
confidence: 99%
“…In the formation of biofilms, adherence of microbes to a surface is followed by cell division and/or capture of free-flowing microbes into the growing biofilm and production of an extracellular matrix of macromolecules. There are functional amyloids present in biofilms made by bacteria and yeast (4)(5)(6)(7). These functional amyloids play roles in cell adhesion and in biofilm matrices (4,5,8).…”
mentioning
confidence: 99%
“…Within the midregions of Als5p, Flo1p, and Flo11p are 6-to 7-amino-acid sequences predicted by TANGO to form amyloids (http://tango.crg.es/) (11,12). The amyloid sequence in Als5p is important for cell-to-cell aggregation and cell-to-substrate adhesion (7). A single-site amino acid substitution in the amyloid region of Als5p V326N decreases in vitro cell-to-cell aggregation, cellto-substrate adhesion, and fluorescence of the amyloid-reporting dye thioflavin T (ThT) (7).…”
mentioning
confidence: 99%